Some issues in the design of predictive controllers - Magni, Lalo; Nicolao, Giuseppe de; Scattolini, Riccardo (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, we discuss how to design a predictive controller capable of addressing a number of important issues ranging from nominal stability to the model identification/controller design interplay. Nominal stability is ensured by resorting to Constrained Receding Horizon Predictive Control. As for robust stability, the connections between the frequency weighting P-polynomial in the cost function and the achievable robustness against multiplicative uncertainty are investigated.
Keywords: predictive control; robust control; two degree of freedom regulation; identification for control